Determinants of birth-control choices among female teachers of child-bearing age in selected secondary schools in Ibadan North Local Government of Oyo State (2013)
This study however focused on determinants of birth control choices among female teachers of child-bearing age in selected secondary school in Ibadan North Local Government of Oyo State. The descriptive survey research design were adoptedfor the study. 429 female teachers of child-bearing age waspurposively selected for the study. Demographie data was analysed using simple percentage and frequency counts while linear regression was used to analyse the hypotheses at 0.05 alpha level. Self developed Likert type questionnaire was used as research instrument. The findings showed the respondents differ significantly, in their responses knowledge of birth control methods (F= 391.21), effectiveness and time duration of birth control methods (F = 233.41), convenience of use (F = 363.21), religious belief spouse influence (F=118.6), peer influence (F=222.6), current number of children (70.12). This showed a relative contribution of the independent variable on the dependent variable. All the seven hypotheses were rejected. Knowledge of birth control methods, effectiveness and time duration of birth control methods, convenience of use, religious belief, spouse influence, peers influence and current number of children were found to be the factors that determine birth control choices among female teachers. It is therefore recommended that health education programmes such as seminars, health talks e.t.c. should be organized for women to create more awareness on the various methods of birth control. This will encourage them on the need for contraception and find solution to various reproductive health challenges.